The Role of Antioxidant to Prevent Free Radicals in The Body - Zulaikhah, Siti Thomas (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
AbstractAntioxidants are compounds that can counteract or reduce the negative impact oxidants in the body. Antioxidants work by donating an electron to compounds that are oxidant so that the oxidant compound activity can be inhibited. Antioxidants are classified into two, namely antioxidant enzymes and non-enzyme. Antioxidant enzymes as enzyme superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx), a non-enzyme antioxidant found in many vegetables and fruits, which include reduced glutathione (GSH), vitamin C, E, Î²- carotene, flavonoids, isoflavones, flavones, antosionin, catechins, and isokatekin, and lipoic acid. Low antioxidant enzymes can be used as a marker of high levels of free radicals in the body. Following review aims to provide an overview of the role of antioxidants in preventing the formation of free radicals in the body.